Multiscale analysis on the wear process of cemented carbide tools during titanium alloy machining - Wenmeng Zhou; Pingfa Feng; Wen Ji; Zhongyu Wang; Yuan Ma; Enlai Jiang; Huiting Zha; Zhipeng Cai; Feng Feng (Friction)
Cemented carbide tools are widely utilized in titanium alloy machining. However, severe tool wear usually occurs during machining; thus, the wear process has attracted widespread attention. Electromagnetic treatment was applied in our previous study to significantly improve the tool life of cemented carbide tools in Ti6Al4V machining. To investigate the effect of electromagnetic treatment on wear performance, a multiscale analysis of the wear process of cemented carbide tools in the turning process, including microdefects and wear topography at various scales, was conducted in the present study. The distribution of dislocations in the tool material was measured through electron backscatter diffraction, and the surface topographies in the wear area during the Ti6Al4V cutting process were recorded via white light interferometry. Fractal analysis based on the scaling property of surface roughness was carried out to further quantify the wear performance of the tools. The results revealed that the wear mechanism of the cutting tools was mainly adhesion and diffusion, and the diffusion wear of the electromagnetically treated tools was less than that of the untreated tools. Based on the multiscale analysis of flank wear, the effect of electromagnetic treatment on the enhancement of the wear resistance of cemented carbide cutting tools was demonstrated. The multiscale analysis of the wear performance of cutting tools in this study effectively revealed the mechanism by which electromagnetic treatment enhances wear resistance, thus contributing to filling the research gap of traditional studies on tool wear that generally employ single scales.